Resin composition, film containing said resin composition and uses thereof

The resin composition, comprising specific propylene and ethylene polymers, addresses the challenges of low-temperature adhesion and whitening in various materials, achieving enhanced performance in food packaging, construction, and secondary battery applications.

JP7661476B2Active Publication Date: 2025-04-14MITSUI CHEMICALS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023506879
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-15
Filing Date
2022-02-15
Publication Date
2025-04-14
Estimated Expiration
2042-02-15

AI Technical Summary

Technical Problem

Existing technologies face challenges in achieving low-temperature adhesion and preventing whitening in food packaging materials, construction and industrial materials, and secondary battery components, particularly during secondary processing such as squeezing and folding.

Method used

A resin composition comprising specific ratios of propylene polymer (A), propylene polymer (B), polyolefin (C) containing structural units derived from unsaturated carboxylic acids, and ethylene polymer (D), which meets certain melting point, MFR, and structural unit content requirements, is used to form films and materials with enhanced adhesion and whitening resistance.

Benefits of technology

The resin composition achieves excellent low-temperature adhesion and prevents whitening during deformation processing, making it suitable for various applications including food packaging, construction materials, and secondary battery components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661476000001
    Figure 0007661476000001
Patent Text Reader

Abstract

A resin composition in which the content of a propylene-based polymer (A) satisfying a given requirement is 10-99.9 parts by mass, the content of a propylene-based polymer (B) satisfying a given requirement is 0-40 parts by mass, the content of a polyolefin (C) having a structural unit derived from an unsaturated carboxylic acid and / or a derivative thereof is 0.1-20 parts by mass, and the content of an ethylene-based polymer (D) satisfying a given requirement is 0-40 parts by mass (the sum of the contents of components (A), (B), (C), and (D) is taken as 100 parts by mass).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a film containing the resin composition, and uses thereof. [Background technology]

[0002] Polypropylene has been widely used as a thermoplastic molding material with excellent rigidity, heat resistance, transparency, and the like. Since polypropylene is a non-polar material, it has poor adhesion to, for example, metal materials such as aluminum and polar materials such as ethylene-vinyl alcohol copolymers. A technique for modifying polypropylene with an unsaturated carboxylic acid or its derivatives for the purpose of improving adhesion is widely known. In addition, since polypropylene has poor flexibility, when it is used as an adhesive resin, a soft rubber component is usually blended with polypropylene. A polypropylene-based adhesive resin with improved adhesion has been proposed by blending a soft rubber component with polypropylene (Patent Document 1).

[0003] In addition, since polypropylene has high gas permeability, when used as a food packaging material, it is often laminated with polar resins such as ethylene-vinyl alcohol copolymer (EVOH), polyamide (PA), and polyester (e.g., polyethylene terephthalate (PET)) that have gas barrier properties in order to maintain the freshness of the contents and extend the expiration date. Such multilayer films are used after being processed into container shapes such as cups and trays by secondary processing such as drawing. Multilayer films for drawing have been proposed, for example, in Patent Document 2.

[0004] Furthermore, polypropylene is also used as a construction and industrial material because it has moderate flexibility, abrasion resistance, scratch resistance, heat resistance, chemical resistance, post-processability, etc. Construction and industrial materials include decorative films that are attached to the surfaces of wood boards, inorganic boards, metal plates, etc. with an adhesive to be used as decorative plates. Patent Document 3 and other documents have proposed a technology in which a pattern layer on a base film constituting a decorative film and a polypropylene protective layer for protecting the pattern layer are bonded via a polypropylene adhesive resin layer.

[0005] On the other hand, for secondary batteries such as lithium ion batteries, metal cans have been used. In recent years, in response to the demand for thinner and more diverse products, laminate packaging materials have been used in which a composite of aluminum foil and a resin film laminated thereon is formed into a bag shape. Metal lead substrates such as aluminum and nickel are attached to the metal substrates of the positive and negative electrodes of lithium ion batteries to extract electricity. In order to prevent short circuits between the lead substrate and the aluminum foil of the laminate packaging material and leakage of electrolyte, it has become common to sandwich and seal the sealing portion of the lead substrate with a film-shaped insulator (tab lead film) in order to improve the sealing strength between the lead substrate and the innermost resin layer (sealant) of the laminate packaging material. Such sealing materials for tab leads such as tab lead films have been proposed, for example, in Patent Documents 4 to 6. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 04-300933 [Patent Document 2] JP 2000-301675 A [Patent Document 3] Patent No. 4803441 [Patent Document 4] JP 2014-210841 A [Patent Document 5] JP 2014-225378 A [Patent Document 6] International Publication No. 2014 / 106887 Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, there has been a demand for improved low-temperature adhesiveness of adhesive films, which can be bonded with less heat in order to improve productivity. Furthermore, films for food packaging materials that are processed into container shapes such as cups and trays, films for building and industrial materials such as decorative films, and secondary battery components such as exterior materials for lithium-ion batteries undergo secondary processing such as drawing and folding, so there is also a demand for preventing whitening during secondary processing. However, it has been difficult to meet this demand with conventional technologies such as Patent Documents 2 to 6.

[0008] The present invention has been made in consideration of the above-mentioned problems, and aims to provide an adhesive resin composition capable of forming food packaging materials, construction and industrial materials, and secondary battery components that have excellent low-temperature adhesion and whitening prevention properties, a film containing the composition, and a food packaging material, construction and industrial materials, and secondary battery components that contain the film. [Means for solving the problem]

[0009] The present inventors have conducted studies to solve the above problems, and as a result, have found that the above problems can be solved by the following aspects, leading to the completion of the present invention. [1] The content of the propylene-based polymer (A) satisfying the following (a) is 10 to 99.9 parts by mass, The content of the propylene-based polymer (B) satisfying the following (b) is 0 to 40 parts by mass, The content of the polyolefin (C) containing a structural unit derived from an unsaturated carboxylic acid and / or a derivative thereof is 0.1 to 20 parts by mass, The content of the ethylene polymer (D) satisfying the following (d) is 0 to 40 parts by mass. (where the total content of components (A), (B), (C) and (D) is 100 parts by mass), (a) A melting point (Tm) measured by differential scanning calorimetry is less than 120°C and is greater than or equal to 100°C; (b) the MFR measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg is in the range of 0.01 to 100 g / 10 min, and the following requirements (b-1) and (b-2) are satisfied; (b-1) The melting point (Tm) observed in differential scanning calorimetry is less than 100°C, or no melting point (Tm) is observed; (b-2) has structural units derived from propylene and structural units derived from at least one olefin selected from ethylene and an α-olefin having 4 to 20 carbon atoms, and the content of structural units derived from ethylene and at least one α-olefin selected from 4 to 20 carbon atoms is 40 mol % or less; (d) An ethylene homopolymer or a copolymer of ethylene and at least one α-olefin selected from α-olefins having 3 to 20 carbon atoms, having an MFR in the range of 0.1 to 10 g / 10 min, measured at 190°C under a load of 2.16 kg in accordance with ASTM D1238.

[0010] [2] The content of the propylene polymer (A) is 10 to 94.9 parts by mass, The content of the propylene polymer (B) is 5 to 40 parts by mass, The content of the polyolefin (C) is 0.1 to 20 parts by mass, The content of the ethylene polymer (D) is 0 to 40 parts by mass. (wherein the total content of components (A), (B), (C) and (D) is 100 parts by mass),

[0011] [3] The content of the propylene polymer (A) is 10 to 94.9 parts by mass, The content of the propylene polymer (B) is 0 to 40 parts by mass, The content of the polyolefin (C) is 0.1 to 20 parts by mass, The content of the ethylene polymer (D) is 5 to 40 parts by mass. (wherein the total content of components (A), (B), (C) and (D) is 100 parts by mass), [4] The density of the ethylene polymer (D) is 0.87 g / cm 3 The resin composition according to [3], [5] A single-layer or multilayer film comprising at least one layer containing the resin composition according to any one of [1] to [4]. [6] A multilayer film comprising at least one layer comprising the resin composition according to any one of [1] to [4] and at least two layers other than the layer comprising the composition, wherein both sides of the layer comprising the composition are in contact with the other layers.

[0012] [7] A multilayer film comprising at least one layer containing the resin composition according to any one of [1] to [4] and at least one layer selected from a metal-containing layer, a polyolefin layer, and a polar resin layer, wherein the layer containing the composition is in contact with at least one of the metal-containing layer, the polyolefin layer, and the polar resin layer. [8] A food packaging material comprising a monolayer or multilayer film according to [5], or a multilayer film according to [6] or [7].

[0013] [9] A building or industrial material comprising a monolayer or multilayer film according to [5] or a multilayer film according to [6] or [7].

[10] A secondary battery member comprising the monolayer or multilayer film according to [5] or the multilayer film according to [6] or [7].

[0014]

[11] The secondary battery member according to

[10] , which is an exterior material for a lithium-ion battery.

[12] The secondary battery member according to

[10] , which is a tab lead film for a lithium ion battery.

[13] A method for producing a monolayer or multilayer film, comprising melt extrusion molding the resin composition according to any one of [1] to [4]. Effect of the Invention

[0015] According to the present invention, it is possible to provide an adhesive resin composition capable of forming food packaging materials, construction and industrial materials, and secondary battery components that have excellent low-temperature adhesion and whitening prevention properties, a film containing the composition, and a food packaging material, construction and industrial materials, and secondary battery components that contain the film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. The resin composition of the present invention contains a propylene-based polymer (A) and a polyolefin (C) containing a structural unit derived from an unsaturated carboxylic acid and / or a derivative thereof, and may further contain a propylene-based polymer (B) or an ethylene-based polymer (D), or a propylene-based polymer (B) and an ethylene-based polymer (D).

[0017] Propylene polymer (A) The propylene polymer (A) may be a propylene homopolymer or a copolymer of propylene and at least one α-olefin other than propylene having 2 to 20 carbon atoms. Examples of the α-olefin other than propylene having 2 to 20 carbon atoms include ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, and ethylene or an α-olefin having 4 to 10 carbon atoms is preferred.

[0018] The copolymer of propylene with these α-olefins may be a random copolymer or a block copolymer. The structural units derived from these α-olefins may be contained in the copolymer of α-olefins and propylene in a proportion of 35 mol % or less, preferably 30 mol % or less.

[0019] The propylene polymer (A) satisfies the following requirement (a). (a) The melting point (Tm) observed by differential scanning calorimetry is less than 120° C. and not less than 100° C. When the melting point (Tm) is within the above range, the resin composition of the present invention has excellent whitening resistance and excellent low-calorie adhesion. The melting point (Tm) is preferably 100 to 115°C, more preferably 100 to 110°C.

[0020] The propylene polymer (A) desirably has a melt flow rate (MFR) measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg in the range of 0.01 to 1000 g / 10 min, preferably 0.1 to 100 g / 10 min.

[0021] The propylene polymer (A) may have either an isotactic structure or a syndiotactic structure, and either structure can be selected in consideration of compatibility with the propylene polymer (B) as described below.

[0022] That is, the form of the propylene polymer (A) includes an isotactic propylene polymer (A1) and a syndiotactic propylene polymer (A2). Examples of the isotactic propylene polymer (A1) include homopolypropylenes having excellent heat resistance, such as known homopolypropylenes having a copolymerization component other than propylene of 3 mol % or less, block polypropylenes having an excellent balance between heat resistance and flexibility, such as known block polypropylenes having a normal decane-eluted rubber component of 3 to 30 mass %, and random polypropylenes having an excellent balance between flexibility and transparency, such as known random polypropylenes having a melting peak measured by a differential scanning calorimeter (DSC) of less than 120°C, 100°C or higher, preferably in the range of 100 to 110°C. In order to obtain the desired physical properties, an appropriate selection can be made from these, or two or more of the above polypropylene components having different melting points or rigidities can be used in combination.

[0023] Such an isotactic propylene polymer (A1) can be produced, for example, by polymerizing propylene or copolymerizing propylene with another α-olefin using a Ziegler catalyst system consisting of a solid catalyst component containing magnesium, titanium, a halogen and an electron donor as essential components, an organoaluminum compound and an electron donor, or a metallocene catalyst system using a metallocene compound as one of the catalyst components.

[0024] The syndiotactic propylene polymer (A2) contains 90 mol % or more of structural units derived from propylene and 10 mol % or less of structural units derived from one or more selected from ethylene and α-olefins having 4 to 20 carbon atoms, and preferably contains 91 mol % or more of structural units derived from propylene and 9 mol % or less of structural units derived from one or more selected from ethylene and α-olefins having 4 to 20 carbon atoms (the total of both structural units is 100 mol %).

[0025] Examples of the α-olefin having 4 to 20 carbon atoms include 1-butene, 3-methyl-1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0026] The syndiotactic propylene polymer (A2) has a melting peak measured by a differential scanning calorimeter (DSC) usually below 120°C and 100°C or higher, preferably in the range of 100 to 110°C. The syndiotactic propylene polymer (A2) can be produced, for example, by using a method such as that described in International Publication No. WO2011 / 078054.

[0027] (B) Propylene-based polymer The propylene polymer (B) satisfies the following requirement (b). (b) The MFR measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg is in the range of 0.01 to 100 g / 10 min, and the following requirements (b-1) and (b-2) are satisfied. (b-1) The melting point (Tm) is less than 100° C., or no melting point is observed. (b-2) It has structural units derived from propylene and structural units derived from ethylene and at least one olefin selected from α-olefins having 4 to 20 carbon atoms, and the content of structural units derived from ethylene and at least one α-olefin selected from 4 to 20 carbon atoms is 40 mol % or less.

[0028] Requirements (b) and other items are explained in detail below. Requirement (b) The melt flow rate (MFR; ASTM D1238, 230° C., under a load of 2.16 kg) of the propylene polymer (B) is from 0.01 to 100 g / 10 min, and preferably from 0.1 to 30 g / 10 min. Further, the propylene polymer (B) satisfies the requirements (b-1) and (b-2).

[0029] (Requirement (b-1)) The melting point (Tm) observed in differential scanning calorimetry is less than 100°C, or no melting point is observed. Here, no melting point is observed means that no crystal melting peak with a crystal melting heat of 1 J / g or more is observed in the range of -150 to 200°C in differential scanning calorimetry. Details of the melting point measurement conditions are as described in the Examples section below.

[0030] The melting point (Tm) is preferably not more than 90° C., more preferably not more than 80° C. If the melting point (Tm) satisfies the above condition, it is preferable from the viewpoints of compatibility with the propylene-based polymer and low-temperature adhesiveness.

[0031] (Requirement (b-2)) It has structural units derived from propylene and structural units derived from ethylene and at least one olefin selected from α-olefins having 4 to 20 carbon atoms, and the content of structural units derived from ethylene and at least one α-olefin selected from 4 to 20 carbon atoms is 40 mol % or less.

[0032] Examples of the α-olefin having 4 to 20 carbon atoms include 3-methyl-1-butene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. As the at least one olefin selected from ethylene and the α-olefin having 4 to 20 carbon atoms, particularly ethylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene are preferred.

[0033] The content of structural units derived from ethylene and at least one α-olefin selected from those having 4 to 20 carbon atoms is preferably 40 mol % or less, and more preferably 35 mol % or less.

[0034] (Other requirements) The density of the propylene polymer (B) measured by JIS K7112 (density gradient tube method) is preferably 0.85 to 0.89 g / cm 3 and more preferably 0.86 to 0.88 g / cm 3 It is. The propylene polymer (B) has an intrinsic viscosity [η] measured in decalin at 135° C. of 0.1 to 10 dL / g, preferably 0.5 to 10 dL / g.

[0035] This propylene polymer (B) has a single glass transition temperature, and the glass transition temperature (Tg) obtained by differential scanning calorimetry (DSC) is usually in the range of −50° C. to 10° C., preferably −45° C. to 5° C., and more preferably −40° C. to 0° C. When the glass transition temperature (Tg) is within the above range, the propylene polymer (B) is excellent in cold resistance and low-temperature characteristics, and therefore it is preferable.

[0036] Differential scanning calorimetry is carried out, for example, as follows: Approximately 10.00 mg of a sample is placed in a dedicated aluminum pan, and using a DSCRDC220 manufactured by Seiko Instruments Inc., the sample is heated from 30° C. to 200° C. at a rate of 200° C. / min, held at 200° C. for 5 minutes, cooled from 200° C. to -100° C. at a rate of 10° C. / min, held at -100° C. for a further 5 minutes, and then heated at a rate of 10° C. / min to obtain the glass transition temperature (Tg) from the endothermic curve.

[0037] The molecular weight distribution (Mw / Mn, polystyrene equivalent, Mw: weight average molecular weight, Mn: number average molecular weight) of the propylene polymer (B) measured by GPC is preferably 3.5 or less, more preferably 3.0 or less. The lower limit is, for example, 1.5 or more.

[0038] The propylene polymer (B) may be partially graft-modified with a polar monomer. Examples of the polar monomer include hydroxyl-containing ethylenically unsaturated compounds, amino-containing ethylenically unsaturated compounds, epoxy-containing ethylenically unsaturated compounds, aromatic vinyl compounds, vinyl ester compounds, and vinyl chloride. The modified propylene polymer (B) is obtained by graft-polymerizing a polar monomer to the propylene polymer (B) described above. When graft-polymerizing a polar monomer to the propylene polymer (B) described above, the polar monomer is usually used in an amount of 0.1 to 10 parts by mass, preferably 0.1 to 5 parts by mass, per 100 parts by mass of the propylene polymer (B). This graft polymerization is usually carried out in the presence of a radical initiator. As the radical initiator, an organic peroxide or an azo compound can be used. The radical initiator can be used by mixing the propylene polymer (B) and the polar monomer as it is, or can be used after dissolving it in a small amount of an organic solvent. The organic solvent can be used without any particular limitation as long as it is an organic solvent capable of dissolving the radical initiator. In addition, a reducing substance may be used when graft-polymerizing a polar monomer onto the propylene polymer (B), which can increase the graft amount of the polar monomer.

[0039] The graft modification of the propylene polymer (B) with a polar monomer can be carried out by a conventionally known method, for example, by dissolving the propylene polymer (B) in an organic solvent, then adding a polar monomer and a radical initiator to the solution, and reacting for 0.5 to 15 hours, preferably 1 to 10 hours, at a temperature of 70 to 200°C, preferably 80 to 190°C. Alternatively, the propylene polymer (B) can be reacted with the polar monomer without a solvent using an extruder or the like to produce a modified propylene polymer (B). This reaction is usually carried out at a temperature above the melting point of the propylene polymer (B), specifically 120 to 250°C, for usually 0.5 to 10 minutes.

[0040] The modification amount (graft amount of polar monomer) of the modified propylene polymer thus obtained is usually 0.1 to 10 mass %, preferably 0.1 to 5 mass %, and more preferably 0.5 to 5 mass %.

[0041] When the propylene polymer composition of the present invention contains the above-mentioned modified propylene polymer, the composition may have excellent adhesion and compatibility with other resins, and may improve the wettability of the surface of a molded article. The propylene polymer (B) can be produced, for example, by using a method such as that described in International Publication No. WO2004 / 087775.

[0042] Preferred embodiments of the propylene polymer (B) include the following propylene-1-butene copolymer (B1), propylene-ethylene copolymer (B2), propylene-ethylene-1-butene copolymer (B3) and atactic propylene homopolymer (B4).

[0043] The propylene-1-butene copolymer (B1) contains structural units derived from propylene in the above-mentioned propylene-based polymer (B) in an amount of 60 to 90 mol %, preferably 70 to 85 mol %.

[0044] The propylene-1-butene copolymer (B1) having such a composition has good compatibility with the propylene polymer (A). The propylene-ethylene copolymer (B2) contains structural units derived from propylene in the above-mentioned propylene-based polymer (B) in an amount of 60 to 95 mol %, preferably 75 to 90 mol %.

[0045] The propylene-ethylene-1-butene copolymer (B3) contains, in the above-mentioned propylene-based polymer (B), 60 to 95 mol %, preferably 70 to 90 mol %, of structural units derived from propylene, 2 to 25 mol %, preferably 5 to 20 mol %, of structural units derived from ethylene, and 3 to 30 mol %, preferably 5 to 25 mol %, of structural units derived from 1-butene.

[0046] The atactic propylene homopolymer (B4) has a mesopentad fraction of 20 to 80%, preferably 30 to 60%, in the above-mentioned propylene polymer (B).

[0047] Polyolefin (C) containing structural units derived from an unsaturated carboxylic acid and / or a derivative thereof The polyolefin (C) is obtained by modifying a polyolefin with an unsaturated carboxylic acid and / or a derivative thereof, and contains structural units derived from the unsaturated carboxylic acid and / or a derivative thereof.

[0048] Examples of the polyolefins to be modified include polypropylene (c1), ethylene-propylene-α-olefin copolymer (c2) and ethylene-α-olefin copolymer (c3).

[0049] The polyolefin (C) may be one type alone or a mixture of two or more types, for example, any one of modified polypropylene (c1), modified ethylene-propylene-α-olefin copolymer (c2), and modified ethylene-α-olefin copolymer (c3), or a mixture of two or more types thereof.

[0050] The polypropylene (c1) is, for example, a propylene homopolymer and / or a propylene-α-olefin copolymer. The α-olefin is not limited, but preferably includes ethylene and α-olefins having 4 to 20 carbon atoms, and these α-olefins may be used alone or in combination of two or more. Preferred α-olefins are ethylene and α-olefins having 4 to 10 carbon atoms, and among these, ethylene and α-olefins having 4 to 8 carbon atoms are particularly suitable. Here, the content of structural units derived from propylene in the propylene-α-olefin copolymer is at least 50 mol % or more and less than 100%.

[0051] The polypropylene (c1) preferably has an intrinsic viscosity [η] of 0.1 to 10 dl / g. When the intrinsic viscosity [η] is in this range, a composition having excellent moldability and mechanical strength can be obtained.

[0052] The method for producing the polypropylene (c1) is not particularly limited, and examples thereof include well-known methods using well-known catalysts such as Ziegler-Natta catalysts and metallocene catalysts. The polypropylene (c1) is preferably a crystalline polymer, and in the case of a copolymer, it may be a random copolymer or a block copolymer. Furthermore, there is no particular restriction on the stereoregularity or molecular weight as long as it satisfies moldability and has a strength that can withstand use when molded into a molded product. It is also possible to use a commercially available resin as it is.

[0053] The ethylene-propylene-α-olefin copolymer (c2) is, for example, defined by the following (i) and (ii). (i) It contains 45 to 90 mol% of structural units derived from propylene, 2 to 25 mol% of structural units derived from ethylene, and 3 to 30 mol% of structural units derived from an α-olefin having a carbon number of 4 to 20. (ii) The intrinsic viscosity [η] in decalin at 135°C is in the range of 0.1 to 10 dl / g.

[0054] As the α-olefin, an α-olefin having 4 to 10 carbon atoms can be suitably used, and one type may be used alone or two or more types may be used. The ratio of structural units derived from each monomer is preferably 60 to 95 mol % of propylene, 2 to 25 mol % of ethylene, and 3 to 30 mol % of α-olefin, and more preferably 70 to 90 mol % of propylene, 5 to 20 mol % of ethylene, and 5 to 25 mol % of α-olefin. Molar % is more preferred.

[0055] With regard to (ii), the intrinsic viscosity [η] is more preferably in the range of 0.5 to 8, and even more preferably in the range of 0.8 to 6. When the intrinsic viscosity [η] is in the above range, an adhesive having an excellent balance between flexibility and mechanical strength and high adhesive strength can be obtained.

[0056] The method for producing the ethylene-propylene-α-olefin copolymer (c2) is not particularly limited, and it can be produced by a well-known method using a well-known catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst.

[0057] The ethylene-propylene-α-olefin copolymer (c2) is not particularly limited in terms of its stereoregularity or molecular weight, so long as it satisfies the moldability requirements and has sufficient strength to withstand use when molded. Commercially available resins can also be used as they are.

[0058] The ethylene-α-olefin copolymer (c3) is, for example, defined by the following (iii) and (iv).

[0059] (iii) It contains 50 to 99 mol % of structural units derived from ethylene and 1 to 50 mol % of structural units derived from an α-olefin having 3 to 20 carbon atoms. (iv) The intrinsic viscosity [η] in decalin at 135° C. is in the range of 0.1 to 10 dl / g.

[0060] The α-olefin is more preferably an α-olefin having 3 to 10 carbon atoms, and may be one type alone or two or more types. The ratio of structural units derived from each monomer is preferably 55 to 98 mol % of ethylene and 2 to 45 mol % of α-olefin, and more preferably 60 to 95 mol % of ethylene and 5 to 40 mol % of α-olefin.

[0061] As for (iv), the intrinsic viscosity [η] is more preferably in the range of 0.5 to 8, and even more preferably in the range of 0.8 to 6. When the intrinsic viscosity [η] is in the above range, a composition having an excellent balance between flexibility and mechanical strength and high adhesive strength can be obtained.

[0062] The method for producing the ethylene-α-olefin copolymer (c3) is not particularly limited, and examples thereof include well-known methods using well-known catalysts such as Ziegler-Natta catalysts and metallocene catalysts.

[0063] The ethylene-α-olefin copolymer (C3) has excellent moldability, and there is no particular restriction on the molecular weight as long as the molded product has sufficient strength to withstand use. Commercially available resins can be used as the ethylene-α-olefin copolymer (C3).

[0064] Examples of the unsaturated carboxylic acid and / or its derivative that modify these polyolefins include unsaturated compounds having one or more carboxylic acid groups, esters of compounds having a carboxylic acid group and alkyl alcohols, and unsaturated compounds having one or more carboxylic acid anhydride groups. Examples of the unsaturated group that the unsaturated compound has include vinyl groups, vinylene groups, and unsaturated cyclic hydrocarbon groups. The unsaturated carboxylic acid and / or its derivative can be used alone or in combination of two or more. Among these, unsaturated dicarboxylic acids or their acid anhydrides are preferred, and maleic acid, nadic acid, or their acid anhydrides are particularly preferred.

[0065] The amount of structural units derived from unsaturated carboxylic acid and / or its derivative contained in polyolefin (C) is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, calculated as structural units derived from maleic anhydride. When the amount of structural units derived from unsaturated carboxylic acid and / or its derivative is within the above range, a resin composition having an excellent balance between moldability and adhesiveness can be obtained.

[0066] In the polyolefin (C), the content of propylene-derived structural units in the structural units excluding the structural units derived from the unsaturated carboxylic acid and / or its derivative is preferably 80 to 100 mol %, more preferably 90 to 100 mol %. When the content of propylene-derived structural units is within the above range, a resin composition having excellent heat resistance can be obtained.

[0067] The method for grafting the unsaturated carboxylic acid and / or its derivative is not particularly limited, and any conventionally known graft polymerization method such as a solution method, a melt kneading method, etc., can be used. For example, there is a method in which a polyolefin is melted, an unsaturated carboxylic acid and / or its derivative is added thereto, and a method in which a polyolefin is dissolved in a solvent to prepare a solution, and an unsaturated carboxylic acid and / or its derivative is added thereto, and a method in which a graft reaction is carried out.

[0068] Ethylene polymer (D) The ethylene polymer (D) satisfies the following requirement (d). (d) An ethylene homopolymer or a copolymer of ethylene and at least one α-olefin selected from α-olefins having 3 to 20 carbon atoms, having an MFR in the range of 0.1 to 10 g / 10 min, measured at 190°C under a load of 2.16 kg in accordance with ASTM D1238.

[0069] The MFR is preferably in the range of 0.1 to 8 g / 10 min, more preferably in the range of 0.1 to 6 g / 10 min. When the MFR is in the above range, a composition having an excellent balance between flexibility and mechanical strength and having high adhesive strength can be obtained.

[0070] The copolymer is preferably an ethylene-α-olefin copolymer containing 50 to 99 mol % of structural units derived from ethylene and 1 to 50 mol % of structural units derived from an α-olefin selected from α-olefins having 3 to 20 carbon atoms.

[0071] In the copolymer, an α-olefin having 3 to 10 carbon atoms is more preferably used as the α-olefin, and one or more kinds within this range may be used alone. The ratio of each monomer component is preferably ethylene: 55 to 98 mol%, α-olefin: 2 to 45 mol%, and more preferably ethylene: 60 to 95 mol%, α-olefin: 5 to 40 mol%. is more preferred.

[0072] The method for producing the ethylene polymer (D) is not particularly limited, and it can be produced by a well-known method using a well-known catalyst such as a high pressure method, a Ziegler-Natta catalyst, or a metallocene catalyst. Furthermore, there is no particular limitation on the molecular weight as long as it satisfies the moldability and has a strength that can withstand use when made into a molded product. It is also possible to use a commercially available resin as it is. The ethylene polymer (D) may be one to which a small amount of maleic anhydride or the like has been grafted, so long as the above conditions are satisfied. In addition, as long as the above conditions are satisfied, it may be one to which a small amount of maleic anhydride or the like has been grafted, and then the graft monomer is further modified with a diamine, carbodiimide, or the like.

[0073] Other Ingredients The resin composition of the present invention may contain other components, such as propylene-ethylene block copolymers, propylene homopolymers, propylene-ethylene random copolymers, propylene-1-butene random copolymers, propylene-ethylene-1-butene random copolymers, styrene-based elastomers, polyethylene, etc., having compositions different from those of the present invention, within the scope of the invention, which does not impair the effects of the present invention. The proportion of other components in the resin composition of the present invention is preferably 20% by mass or less.

[0074] In addition, known additives such as antioxidants, ultraviolet absorbers, neutralizing agents, nucleating agents, light stabilizers, antistatic agents, antiblocking agents, lubricants, odor absorbents, antibacterial agents, pigments, inorganic and organic fillers, and various synthetic resins may be contained as necessary.

[0075] resin composition The resin composition of the present invention can be produced by a conventional method, for example, by melt-kneading the above-mentioned components.

[0076] The contents of the propylene polymer (A), the propylene polymer (B), the polyolefin (C), and the ethylene polymer (D) in the resin composition of the present invention are, when the total content of the propylene polymer (A), the propylene polymer (B), the polyolefin (C), and the ethylene polymer (D) is taken as 100 parts by mass, 10 to 99.9 parts by mass of the propylene polymer (A), 0 to 40 parts by mass of the propylene polymer (B), 0.1 to 20 parts by mass of the polyolefin (C), and 0 to 40 parts by mass of the ethylene polymer (D); It is preferable that the propylene-based polymer (A) is 10 to 94.9 parts by mass, the propylene-based polymer (B) is 5 to 40 parts by mass, the polyolefin (C) is 0.1 to 20 parts by mass, and the ethylene-based polymer (D) is 0 to 40 parts by mass. More preferably, the propylene-based polymer (A) is 10 to 89.5 parts by mass, the propylene-based polymer (B) is 5 to 40 parts by mass, the polyolefin (C) is 0.5 to 20 parts by mass, and the ethylene-based polymer (D) is 5 to 40 parts by mass. More preferably, the propylene polymer (A) is 20 to 84 parts by mass, the propylene polymer (B) is 10 to 35 parts by mass, the polyolefin (C) is 1 to 20 parts by mass, and the ethylene polymer (D) is 5 to 35 parts by mass.

[0077] In another preferred embodiment, the propylene polymer (A) is 10 to 94.9 parts by mass, the propylene polymer (B) is 0 to 40 parts by mass, the polyolefin (C) is 0.1 to 20 parts by mass, and the ethylene polymer (D) is 5 to 40 parts by mass. The density of the ethylene polymer (D) is 0.87 g / cm. 3 It is also a more preferred embodiment that the density of the ethylene polymer (D) is 0.87 g / cm or less. 3 When the density is less than 0.80 g / cm 3 More preferably, it is equal to or greater than this.

[0078] When the content of the above components in the resin composition of the present invention is within the above range, the adhesion, particularly the adhesion at low heat, specifically the adhesion at 140°C or less, is high, and a film including a layer obtained from this composition is less likely to whiten during deformation processing.

[0079] The resin composition of the present invention preferably has an MFR of 0.1 g / 10 min to 30 g / 10 min, more preferably 1 g / 10 min to 20 g / 10 min, as measured at 230 ° C. and a load of 2.16 kg in accordance with ASTM D1238. When the MFR is within the above range, a resin composition applicable to various film forming methods such as a casting method, an inflation method, and an extrusion lamination method can be obtained. In addition, even if film forming is performed under high-speed forming conditions, the orientation of the molecular chains is easily relaxed, and whitening during subsequent deformation processing can be suppressed.

[0080] Whitening during deformation occurs when fine cracks occur in the film, which is thought to cause a deterioration in insulation when used as battery packaging.

[0081] Single or multi-layer film The monolayer and multilayer films of the present invention are monolayer or multilayer films containing at least one layer containing the resin composition. That is, the monolayer film of the present invention is a film consisting of a layer containing the resin composition, and the multilayer film is a multilayer film containing at least one layer containing the resin composition.

[0082] The monolayer and multilayer films of the present invention have excellent resistance to whitening during deformation processing. Therefore, when the monolayer and multilayer films of the present invention are used as food packaging materials, construction and industrial materials, and secondary battery components such as lithium ion battery components, whitening is unlikely to occur during secondary processing of the film such as drawing and folding. Therefore, the monolayer and multilayer films of the present invention can be suitably used as food packaging materials, construction and industrial materials, and secondary battery components.

[0083] In particular, polypropylene-based resins have been used so far as packaging materials for forming exterior bodies of lithium-ion batteries. However, the present invention uses the specific combination of the above-mentioned propylene-based polymer (A), propylene-based polymer (B), polyolefin (C) and ethylene-based polymer (D) to achieve prevention of whitening, which could not be prevented by conventional polypropylene-based resins.

[0084] The multilayer film of the present invention includes, for example, at least one layer containing the resin composition, and one or both sides of the layer containing the composition are in contact with other layers contained in the multilayer film. Examples of the other layers in contact with the layer containing the composition include a metal-containing layer, a polyolefin layer, and a polar resin layer. Examples of the metal-containing layer include an aluminum layer, a copper layer, and a stainless steel layer, and examples of the polyolefin layer include a polypropylene layer, a poly-4-methylpentene layer, and a polyethylene layer, and examples of the polar resin layer include a polyamide layer, an EVOH layer, a PET layer, and a PBT layer.

[0085] The monolayer and multilayer films of the present invention can be obtained by melt extrusion molding, and can be produced by a casting method, an inflation method, an extrusion lamination method or the like which are generally used industrially.

[0086] <Secondary battery materials> Examples of secondary battery components, which are applications of the film of the present invention, include tab lead films for lithium ion batteries (hereinafter also simply referred to as "tab lead films"), exterior materials for lithium ion batteries (hereinafter also simply referred to as "exterior materials"), etc. Here, the tab lead is a terminal that transfers electricity between an electrode in a battery and the outside, and has a metal layer that is a lead substrate, and a tab lead film formed on at least one side of the lead substrate.

[0087] In the tab lead film of the present invention, the layer (film) made of the composition of the present invention is in contact with the lead substrate, and may have other layers as necessary. The tab lead film is formed to cover a part of the lead substrate (lead conductor) and to adhere to the inner surface of the exterior material of a lithium ion battery. Since the tab lead film of the present invention has excellent low-temperature adhesion, the adhesion temperature with the lead substrate can be lower than that of the conventional one, and as a result, the thermal load during adhesion can be reduced and the productivity can be improved. Here, the adhesion temperature with the lead substrate is not particularly limited as long as it is a temperature at which the tab lead film melts, but is preferably 100 to 200°C, more preferably 130°C to 180°C. In addition, the heating time is also not particularly limited, but is preferably 1 second to 10 minutes, more preferably 1 second to 1 minute.

[0088] One embodiment of the tab lead film of the present invention is a laminated film having an adhesive layer made of the composition of the present invention and a heat-resistant layer. In a lithium-ion battery, the adhesive layer is adhered to a lead substrate, and the heat-resistant layer is adhered to the inner surface of an exterior material.

[0089] The lead substrate connected to the positive electrode of the lithium ion battery is, for example, a lead conductor made of aluminum, titanium, or an alloy containing at least one selected from these materials.The lead substrate connected to the negative electrode of the lithium ion battery is, for example, a lead conductor made of copper, nickel, or an alloy containing at least one selected from these materials.

[0090] The heat-resistant layer may be, for example, a layer made of a polyolefin resin. Examples of such polyolefin resins include thermoplastic polyolefin resins such as polyethylene and polypropylene. These may be used alone or in combination of two or more. The use of a polypropylene resin is preferable from the viewpoint of heat resistance. The polyolefin resin may also be crosslinked.

[0091] The embodiment of the packaging material of the present invention is not particularly limited as long as it has an adhesive layer made of the composition of the present invention, and examples thereof include laminate films having a structure such as a base layer / aluminum foil layer / adhesive layer / sealant layer, etc. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0093] [Physical property measurement conditions] <Melt flow rate (MFR)> According to ASTM D1238, the MFR of the propylene-based polymer was measured at 230° C. under a load of 2.16 kg, and the MFR of the ethylene-based polymer was measured at 190° C. under a load of 2.16 kg.

[0094] <density> The density was measured in accordance with JIS K7112 (density gradient tube method).

[0095] <Polyolefin composition> The content ratio of α-olefin-derived structural units and ethylene-derived structural units in polyolefins is quantified as follows: 13 C-NMR was performed using the following equipment and conditions.

[0096] A JECX400P nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. was used. A mixed solvent of heavy orthodichlorobenzene / heavy benzene (80 / 20% by volume) was used as the solvent. The sample concentration was 60 mg / 0.6 mL, the measurement temperature was 120 °C, and the observation nuclei were 13The conditions used were: C (100 MHz), sequence: single pulse proton decoupling, pulse width: 4.62 μs (45° pulse), repetition time: 5.5 s, number of accumulations: 8000, and chemical shift reference value: 29.73 ppm.

[0097] <Melting point> The melting point was measured using a differential scanning calorimeter (DSC) as follows: Approximately 5 mg of sample was sealed in an aluminum pan and heated from room temperature to 230°C at 10°C / min, and the sample was held at 230°C for 10 minutes to completely melt it. It was then cooled to -20°C at 10°C / min and held at -20°C for 10 minutes, after which the sample was heated again to 230°C at 10°C / min. The peak temperature in this second heating test was taken as the melting point (Tm).

[0098] <Amount of graft modification> The amount of structural units derived from unsaturated carboxylic acids and / or their derivatives (graft modification amount) was measured by an infrared absorption analyzer using a peak derived from the structural units (1790 cm when maleic anhydride was used). -1 ) was measured and quantified using a previously prepared calibration curve.

[0099] <Whitening resistance> The adhesives obtained in the Examples and Comparative Examples were extruded at 240° C. using a T-die extruder with a screw having a diameter of 50 mm and an effective length L / D=28 to produce a monolayer film having a thickness of 100 μm.

[0100] From the obtained monolayer film, JIS K6251 No. 2 dumbbells were punched out parallel to the flow direction of the monolayer film, and the hue L value was measured by the regular reflection light removal method of a spectrophotometer CM-3700A manufactured by Konica Minolta. Furthermore, the hue L value of the JIS K6251 No. 2 dumbbells stretched and deformed by 5 mm, 10 mm, or 20 mm at a crosshead speed of 200 mm / min was measured using a tensile tester. The change in hue L value after 5 mm stretching was defined as ΔL (5 mm), the change in hue L value after 10 mm stretching was defined as ΔL (10 mm), and the change in hue L value after 20 mm stretching was defined as ΔL (20 mm).

[0101] <Film formability> The adhesives obtained in the examples and comparative examples were extruded at 240°C using a T-die extruder with a screw having a diameter of 50 mm and an effective length L / D of 28, and taken up with a cooling roll set at 25°C to form a single-layer film of 100 μm. The single-layer films were formed under three conditions of take-up speeds of 5 m / min, 10 m / min, and 20 m / min. The film formability of the single-layer films obtained under each condition was evaluated according to the following criteria. Formability: No peeling marks were observed on the film surface when passing through the cooling roll. Formability Δ: slight peeling marks were observed on the film surface when passing through the cooling roll. Formability ×: Significant peeling marks were observed on the film surface when the film passed through the cooling roll.

[0102] <Adhesive strength> The adhesive obtained in the Examples and Comparative Examples and commercially available polypropylene (F327, MFR: 7, manufactured by Prime Polymer Co., Ltd.) were co-extruded at 240°C using a T-die extruder with a screw diameter of 50 mm and effective length L / D = 28. The extruded adhesive and polypropylene were laminated in a feed block so that the adhesive was the inner layer and the polypropylene was the outer layer, producing a 100 μm thick multilayer film with inner and outer layers both of 50 μm thick.

[0103] The inner layer of the obtained multilayer film was overlapped with the aluminum foil layer of a commercially available aluminum laminate film (aluminum foil / polyethylene terephthalate: 20 / 12 μm), and a composite was produced by heat sealing using a heat sealer under the following conditions: sealing temperature: 120°C, 130°C, or 140°C, sealing pressure: 0.1 MPa, and sealing time: 10 seconds.

[0104] The adhesive strength (unit: N / 15 mm) of the composite obtained at each sealing temperature was measured using a tensile tester by the T-peel method at room temperature of 23° C. The crosshead speed was 300 mm / min.

[0105] [Polyolefin used] The polyolefins used in the examples and comparative examples are shown below. Unless otherwise specified, all of these polyolefins were prepared by polymerization according to conventional methods. PP-1: Metallocene-based random polypropylene (MFR:8g / 10min, density:0.89g / cm 3 , Propylene content: 94 mol%, Ethylene content: 6 mol%, melting point: 105℃) PP-2: Metallocene-based random polypropylene (MFR:7g / 10min, density:0.90g / cm 3 , Propylene content: 96 mol%, Ethylene content: 4 mol%, melting point: 125℃) PP-3: Metallocene-based random polypropylene (MFR:7g / 10min, density:0.89g / cm 3 , Propylene content: 85 mol%, 1-butene content: 15 mol%, melting point: 98°C) · PBR: Propylene-1-butene random copolymer (MFR:7g / 10min, density:0.88g / cm 3 , Propylene content: 74 mol%, 1-butene content: 26 mol%, melting point 75℃) PER: Propylene-ethylene random copolymer (MFR:7g / 10min, density:0.87g / cm 3 , Propylene content: 84 mol%, Ethylene content: 16 mol%, melting point: 60°C) Modified PP: Modified homopolypropylene (MFR: 100g / 10 minutes, density: 0.90g / cm 3 , maleic anhydride graft amount: 1.5% by mass) EPR: Ethylene-propylene random copolymer (MFR: 0.6g / 10min, density: 0.87g / cm 3 , Ethylene content: 80mol% , propylene content: 20 mol%)

[0106] [Example 1] <Adhesive manufacturing> 80 parts by mass of PP-1, 10 parts by mass of EPR, and 10 parts by mass of modified PP were melt-kneaded at 230° C. using a single-screw extruder to obtain a resin composition. This composition was designated as adhesive 1.

[0107] [Examples 2 to 4, Comparative Examples 1 to 5] In Examples 2 to 4 and Comparative Examples 1 to 5, resin compositions were produced in the same manner as in Example 1 according to the formulations shown in Table 1. The composition obtained in Example 2 was designated Adhesive 2, the composition obtained in Example 3 was designated Adhesive 3, the composition obtained in Example 4 was designated Adhesive 4, the composition obtained in Comparative Example 1 was designated Adhesive 5, the composition obtained in Comparative Example 2 was designated Adhesive 6, the composition obtained in Comparative Example 3 was designated Adhesive 7, the composition obtained in Comparative Example 4 was designated Adhesive 8, and the composition obtained in Comparative Example 5 was designated Adhesive 9.

[0108] The MFR and density of the adhesives obtained in the examples and comparative examples, the evaluation results of the whitening resistance and formability of the monolayer films obtained from these adhesives, and the evaluation results of the adhesive strength of the multilayer films obtained from these adhesives are shown in Table 1. Note that the adhesive strength of Adhesive 9 was not measured because the film surface was roughened due to peel marks during the production of the multilayer film.

[0109] [Table 1]

Claims

1. The content of the propylene-based polymer (A) satisfying the following (a) is 10 to 94.9 parts by mass, The content of the propylene-based polymer (B) satisfying the following (b) is 0 to 40 parts by mass, The content of the polyolefin (C) containing a structural unit derived from an unsaturated carboxylic acid and / or a derivative thereof is 0.1 to 20 parts by mass, The content of the ethylene polymer (D) satisfying the following (d) is 5 to 40 parts by mass. (wherein the total content of components (A), (B), (C) and (D) is 100 parts by mass), a resin composition: (a) a melting point (Tm) measured by differential scanning calorimetry of less than 120°C and equal to or greater than 100°C; (b) the MFR measured in accordance with ASTM D1238 at 230° C. under a load of 2.16 kg is in the range of 0.01 to 100 g / 10 min, and the following requirements (b-1) and (b-2) are satisfied: (b-1) The melting point (Tm) observed in differential scanning calorimetry is less than 100°C, or no melting point (Tm) is observed; (b-2) has structural units derived from propylene and structural units derived from at least one olefin selected from ethylene and an α-olefin having 4 to 20 carbon atoms, and the content of structural units derived from ethylene and at least one α-olefin selected from 4 to 20 carbon atoms is 40 mol% or less; (d) An ethylene homopolymer or a copolymer of ethylene and at least one α-olefin selected from α-olefins having 3 to 20 carbon atoms, having an MFR in the range of 0.1 to 10 g / 10 min as measured at 190° C. under a load of 2.16 kg in accordance with ASTM D1238.

2. The density of the ethylene polymer (D) is 0.87 g / cm 3 The resin composition according to claim 1, wherein:

3. A single-layer or multi-layer film comprising at least one layer comprising the resin composition according to any one of claims 1 to 2.

4. A multilayer film comprising at least one layer comprising the resin composition according to any one of claims 1 to 2, and at least two layers other than the layer comprising the composition, wherein both sides of the layer comprising the composition are in contact with the other layers.

5. A multilayer film comprising at least one layer comprising the resin composition according to any one of claims 1 to 2, and at least one layer selected from a metal-containing layer, a polyolefin layer, and a polar resin layer, wherein the layer comprising the composition is in contact with at least one of the metal-containing layer, the polyolefin layer, and the polar resin layer.

6. A food packaging material comprising the monolayer or multilayer film of claim 3 or the multilayer film of claim 4 or 5.

7. 6. A construction or industrial material comprising the monolayer or multilayer film according to claim 3 or the multilayer film according to claim 4 or 5.

8. A secondary battery member comprising the monolayer or multilayer film according to claim 3 or the multilayer film according to claim 4 or 5.

9. The secondary battery member according to claim 8, which is an exterior material for a lithium ion battery.

10. 9. The secondary battery member according to claim 8, which is a tab lead film for a lithium ion battery.

11. A method for producing a monolayer or multilayer film, comprising melt extruding the resin composition according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • Polymer composition

    JP1992300933A

  • Laminate and sealed container

    JP2000301675A

  • Modified polyolefin composition and laminate using the same

    JP2004269688A

  • Polyolefin resin composition and molded article containing the same

    JP2013241589A

  • Tab lead sealing adhesive film comprising modified polyolefin-based resin with thermal adhesiveness

    JP2014210841A